Protective effect of caffeic acid phenethyl ester (CAPE) on myocardial ischemia-reperfusion-induced apoptotic cell death - Parlakpinar, H; Sahna, E; Acet, A; Mizrak, B; Polat, A (Elsevier Ireland Ltd, 2005)
Occlusion of coronary artery causes cardiomyocyte dysfunction. Reperfusion relieves ischemia by providing cells with metabolites and oxygen, thereby preventing extensive tissue damage. Although reperfusion salvages the myocardium, it also initiates a series of events including myocardial apoptosis and necrosis. The common inducers of apoptosis include reactive oxygen species (ROS). Caffeic acid phenethyl ester (CAPE) is known as an antioxidative, anti-inflammatory effects, may protect myocardial ischemia-reperfusion (MI/R)-induced apoptosis. We have previously reported that CAPE reduced MI/R-induced necrosis. Therefore, this study was focused to investigate protective effect of CAPE on the distinct form of cell death; apoptosis in an in vivo rat model. To produce MI/R, a branch of the descending left coronary artery was occluded for 30 min followed by 2 h reperfusion. ECG changes, blood pressure (BP), and heart rate (HR) were measured before occlusion and continued both occlusion and reperfusion. CAPE (50 mu mol/kg) was given 10 min before ischemia via juguler vein. Extensive formation of DNA strand breaks, the typical biochemical feature of apoptosis, was detected with the use of the terminal deoxynucleotidyl transferase (TdT)-mediated d UTP-biotin nick and labeling (TUNEL) method. Also, cysteine aspartate specific proteinase (caspase)-3 and caspase-9 activities a universal effector of apoptosis, were determined. Trunk blood was extracted to determine the serum contents related to oxidant-antioxidant status. In hemodynamic parameters, there was no significant difference in HR or BP values among any group. CAPE administration had no a significant effect on hemodynamic parameters during ischemia or reperfusion. Control group revealed extensive TUNEL-positive cardiomyocytes especially in free wall of left ventricule, interventiculare septum and nearly apex zone. Intensity of TUNEL-positive cardiomyocytes reduced as a result of CAPE treatment compared to control group in the same sections. Result of the caspase activities was found to correlate with TUNEL evaluation. CAPE also, ameliorated antioxidant status. We propose that CAPE acts in the heart as a potent scavenger of free radicals to prevent the apoptotic effect of I/R. Further studies are needed to elucidate the mechanisms of apoptotic death machinery. (C) 2004 Elsevier Ireland Ltd. All rights reserved.
Keywords: apoptosis; caffeic acid phenethyl ester (CAPE); reactive oxygen radicals; rat